Step-by-step explanation:
Let's solve your equation step-by-step.
2(x+2)−3(x−3)=x+7
Step 1: Simplify both sides of the equation.
2(x+2)−3(x−3)=x+7
(2)(x)+(2)(2)+(−3)(x)+(−3)(−3)=x+7(Distribute)
2x+4+−3x+9=x+7
(2x+−3x)+(4+9)=x+7(Combine Like Terms)
−x+13=x+7
−x+13=x+7
Step 2: Subtract x from both sides.
−x+13−x=x+7−x
−2x+13=7
Step 3: Subtract 13 from both sides.
−2x+13−13=7−13
−2x=−6
Step 4: Divide both sides by -2.
−2x
−2
=
−6
−2
x=3
Answer:
x=3
Answer:
22=-7
Step-by-step explanation:
Answer:
Step-by-step explanation:
Fifth root of m³⁵ = (m³⁵)^(⅕) = m^(35/5) = m⁷
What statements? Please include a explanation to include the information
Answer:
106
Step-by-step explanation:
Given:
Thirteen fewer than three times his thinking number is 305.
Question asked:
What number is Tomás thinking ?
Solution:
Let Toma's thinking number be 
As 13 fewer than 3 times his thinking number is 305.
The equation will be:


Adding both side by 13

Dividing both side by 3

Thus, Tomàs was thinking of a number is 106